Parametric study of biomass oil (palm kernel shell oil) based bioadhesive formulation / Nur Aliah Mohd Arish - Mohd Arish, Nur Aliah (2017)
Adhesives are used widely in the wood, metal, paper, leather, rubber and glass industries, the demand for these liquid natural adhesives gradually increases from time to time, however, its dependent on the supply of petroleum suffers an impact due to its high cost and depletion of this nonrenewable source. Thus, allowing biomass material as a substitute for the production of phenol formaldehyde as the main material in producing bio adhesive. Palm kernel shell is a renewable source of biomass that can be used and now its potential to be a bio adhesive material are being utilized. With resort to this material as a green technology that helps preserve the environment as it lessen the amount of solid waste, it also caused less pollution and not harmful to human health.In this study, the PKS oil produced through the process of updraft gasification is utilized for the production of bio based phenolic resin. This study will compare the physical and chemical properties of the bio based phenolic resins derived from the palm kernel shell with the reference phenol formaldehyde. It is also carried out to formulate, from palm kernel shell oil a bio based adhesive on a different set of parameters (temperature, time and catalyst loading) with comparison study to the reference phenol formaldehyde adhesive. Characterization of chemical characteristics using GCMS to analyze the amount of phenol content in the bio adhesive. Overall results shows that the best conditions of formulation in producing bio based phenolic resin is at 85°c temperature, with time of 60 min and catalyst loading of 0.6g at this point the highest value of phenol can be obtained. In conclusion, PKS oil shows that it is suitable as a substitute for commercial adhesive.